Habitação, desorganização social e violência: situação e perspectiva no bairro Benedito Bentes, Maceió-AL - Gomes, Jairo da Silva (2018)
The text examines the trajectory of the largest cluster and most notable instance of social housing in the city of Maceió / AL, the neighborhood of Benedito Bentes. It tries to trace how the transformations in its social composition in parallel with the evolution of the homicides has influenced in the way the residents deal with the derogatory visibility attached to their place of residence. Precisely because of this, the main question that arose was to know how the narrative of these could illuminate the conditions that had to be combined so that violence and crime, encompassed by a range of concerns, has acquired special importance in the neighborhood. This problematic suggests, at first, two hypotheses: on the one hand, social relations are strongly destabilized due to the continuous migratory process for the region; On the other hand, violence constitutes, in this logic, a response to the processes of social (re) adaptation and (re) structuring of the neighborhood. Thus, a case study was carried out, with an ethnographic basis, based on a set of residents and community leaders. In the final considerations, it was verified that for several residents, the local violence, in addition to the recurrent drug trafficking discourse, is the result of a series of socially stigmatized state experiments, through which urban development and some policies directed to the region are questioned.